Scopolin ameliorates high-fat diet induced hepatic steatosis in mice: potential involvement of SIRT1-mediated signaling cascades in the liver - Ahyoung Yoo (Nature Portfolio, 2017)
Abstract The present study aimed to investigate whether scopolin exhibits beneficial effects on high-fat diet (HFD)-induced hepatic steatosis in mice. The involvement of sirtuin 1 (SIRT1) as a molecular target for scopolin was also explored. Scopolin decreased the Km of SIRT1 for p53 and nicotinamide adenine dinucleotide without altering Vmax in a cell-free system. Scopolin alleviated oleic acid-induced lipid accumulation and downregulation of SIRT1 activity in HepG2 cells, and these beneficial effects of scopolin were abolished in the presence of SIRT1 inhibitor. Mice administered 0.02% scopolin for 8 weeks exhibited improved phenotypes of HFD-induced hepatic steatosis along with increased hepatic SIRT1 activity and protein expression. Scopolin resulted in increased deacetylation of sterol regulatory element-binding protein 1c with subsequent downregulation of lipogenic genes, and enhanced deacetylation of protein peroxisome proliferator-activated receptor-γ coactivator 1α with upregulation of fatty acid oxidation genes in livers. Scopolin also enhanced deacetylation of nuclear factor-kappa enhancer binding protein and liver kinase B1 (LKB1), facilitating LKB1/AMP-activated protein kinase signaling cascades. Scopolin attenuated hepatic steatosis through activation of SIRT1-mediated signaling cascades, a potent regulator of lipid homeostasis. Increased hepatic SIRT1 activity and protein expression appeared to be associated with these beneficial effects of scopolin.